Local Elastic Stress Approach for Fatigue Life Calculation by the Finite Element Method (FEM) - Milan Ruzicka (Communications - Scientific letters of the University of Zilina, 2004)
The paper discusses possibilities of a description of material fatigue and prediction of service life of machine parts on the basis of stress state calculations using the finite element method (FEM). It focuses on the local approach to the assessment of service life that is based on the determination of elastic stress peaks in stress raisers (notches) and on the derivation of the fatigue stress curves for assessed structural points. The method of taking into account the stress concentration and stress gradient during the determination of synthetic fatigue curves is described. Furthermore, methods of processing the loading history and correcting mean stress values of loading cycles are described.